Penerapan Metode Talking Stick dalam Meningkatkan Hasil Belajar IPS Tema 5 Bangga Sebagai Bangsa Indonesia Pada Peserta Didik Kelas V B SD Negeri Kasreman di Semester I Tahun Pelajaran 2018/2019 - Arifin, Mohamad Zainul (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The type of this research is a Class Action Research (CAR) with the purpose toanalyze the application of talking stick method in the learning of social science on the fifthchapter about the pride as Indonesian in increasing the learning outcome of the students ofClass V B the Elementary School of Kasreman on the first Semester of the 2018/2019 yearacademic. The subjects of this research are the students of Class V B the Elementary School ofKasreman on the first Semester of the 2018/2019 year academic as much as twenty fivechildren; consist of twelve boys and ten girls. The data resources of this research are relatingwith learning activities and learning outcomes. Techniques of collecting data of this researchare non test technique and test technique. Technique of analyzing data of this research iscomparative description. The procedure of this research is the cycle model. The results of thisresearch are 1) the application of talking stick method in the learning of social science on thefifth chapter about the pride as Indonesian is a different task with conceptual picture for eachgroup, 2) the applications of talking stick method in the learning of social science on the fifthchapter about the pride as Indonesian are a grouptasks; discussing with the group, giving fourinformation relating with the conceptual picture, asking only the most difficult question andanswering the questions from other groups’, 3) the applications of talking stick method in thelearning of social science on the fifth chapter about the pride as Indonesian are increasing thelearning activities in discussing, answering the questions form the teacher and other students,asking the continuation questions and declaring the opinions and 4) the applications of talkingstick method in the learning of social science on the fifth chapter about the pride as Indonesianare increasing the learning outcomes. The learning outcomes on the Early Condition are 56,63for the average and 31,81% for the completeness. The learning outcomes on the First Cycle are69,09 for the average and 59,09% for the completeness. The learning outcomes on the SecondCycle are 80,9 for the average and 86,36% for the completeness.